Effects of underburning on habitat use of mule deer during migration - Carolyn A. Eckrich; Priscilla K. Coe; Ryan M. Nielson; Darren A. Clark; Bruce K. Johnson (Wildlife Society Bulletin)
ABSTRACT Mule deer (Odocoileus hemionus hemionus) populations have been declining throughout their range and deteriorating habitat conditions are likely one cause of these declines. Reductions in food and cover availability along traditional routes may especially influence habitat use during migration by mule deer. Forest management practices such as underburning, the practice of using low‐severity fires to reduce fuel loads, are often assumed to be beneficial to deer through enhancement of forage quality and quantity. However, these practices may be detrimental to mule deer through decreases in food and cover availability. Currently, little is known about the effects of underburning on habitat use by mule deer during migration. We analyzed Global Positioning System tracking data from 187 adult female mule deer in central Oregon, USA, from 2005 to 2012 in relation to 243 areas that were underburned between 1977 and 2009 to assess effects of underburning on habitat use during seasonal migrations. During spring migration, mule deer decreased use of recently underburned (i.e., ≤7 years‐since‐burned) areas compared with pretreatment use. There was not a difference in use of recently underburned areas before and after treatment during autumn migration. In spring, the proportion of used underburned areas declined postburn without recovering to preburn levels up to 20 years after treatment. The proportion of underburned areas used in autumn was much more variable, with use of postburn areas fluctuating above the preburn mean but never reaching the preburn maximum. We contend that reductions in forage and cover availability from underburning may negatively affect migrating mule deer, especially during spring. Thus, efforts should be taken to minimize burning large, continuous areas along migration routes and avoid burning adjacent areas during the same year to maintain a diverse mosaic of understory age classes, which will allow deer to make habitat use choices during migration. © 2019 The Wildlife Society.